An Analysis Of Renewable Energy Improvement Using Hybrid Capacitor Solar Cell Method - Rizky Julio Efendi; Solly Aryza; Dino Erivianto (Jurnal Scientia, 2024)
This study aims to analyze the increase in the use of renewable energy through the application of the Hybrid Capacitor Solar Cell method. Solar cells are one of the most potential renewable energy sources, but their storage efficiency is still a challenge, especially in terms of unstable energy availability because it depends on the intensity of sunlight. This study uses a simulation approach to test the performance of the hybrid capacitor-solar cell method. The system is designed to optimize energy storage in capacitors when energy production from solar cells is excessive and provide energy reserves when sunlight intensity is low. The results of the study show that this hybrid method is able to increase energy storage efficiency by up to 30% compared to the use of conventional solar cells that only rely on batteries. In addition, this hybrid system is also able to extend the life of energy storage devices and reduce dependence on chemical batteries, which generally have limited lifespan and environmental impacts. Conclusion of this study is that the Hybrid Capacitor Solar Cell method has great potential in increasing the efficiency of renewable energy and can be a sustainable solution to increase the utilization of solar energy. The implementation of this technology is expected to help accelerate the transition to clean energy and reduce dependence on fossil energy sources.